Exclusão escolar: representações sociais de professores e gestores escolares - Marcon, Patrícia de Fátima Rodrigues (2006)
This research aims to analyze the schoolteachers and principals’ social representations of the Fundamental teaching level school about the school exclusion. This way it has been utilized in audio recorded semi-structured interviews and then it has been written. Sixty-seven educators participated in this work between teachers and principals from fourteen municipal schools, chosen one from each sector of the city of Ponta Grossa urban area in State of Parana. This study is marked by the way of the changing of organization, from the first phase of Fundamental teaching of the serial system to the cycle’s regime of learning, with the enlargement of the Fundamental teaching of eight to nine years occurred in the period from two thousand one to two thousand and four. This new way of school organization brought the necessity to rethink other school aspects and practices in this teaching web, as the classifying evaluation that failed the students didn’t succeed with the mark over fifty at the end of the school year. The effort to examine the teachers and principal social representations can mean an important contribution to study the relations between public policy and the school everyday. With no intention to finish the analysis of this complex phenomenon that is the school exclusion, this work focuses some relevant aspects to the learning problems in a perspective that articulates the implemented public policy and the way the school organizes the guidelines from Municipal Secretary ship of Education – MSE. It believes that as those guidelines consider the teachers and principals’ conceptions will decrease the resistance to changing proposals that affect the school culture. The social representations that came from the teachers report were jointed into four thematic nucleuses: social representation of the child with learning difficulties, social representation of family, social representation of school, social representation of school and social representation of the teaching profession. Each nucleus pointed has subcategories of analyses of social representation those show the way the Fundamental teaching’ teachers and principals understand the things related to school exclusion. The educational policy implemented in the municipal district put in conflict some teachers conceptions about the teaching-learning process. The research has revealed that the effectiveness of the inclusive education policy demands changing of mentality as well as, physical and material structure and human resources. Besides the teachers’ background to work with the learning difficulties, coming from special necessities or not, to contend the school exclusion is a public policy object. This research intends to provoke important reflections to the debate around the school exclusion that that permeates the planning and the implementation of the educational policies.